Produção e caracterização de liga multicomponente duplex do sistema CrCoNi com composição Cr51,5Ni33,5Co15 - Assis, Flávio Fávaro de (Universidade Federal de São Carlos, 2022)
Multicomponent and/or high entropy alloys (HEAs) are a new class of materials that do not have a main element and are instead composed of concentrated solid solutions. Several compositions with interesting mechanical and functional properties have been found, in the literature special focus is given to multicomponent alloys composed of 3d transition metals from the periodic table. Among these alloys, several CrCoNi compositions stand out for their excellent strength, ductility and corrosion resistance. The main focus of the development of these alloys was the pursuit for compositions that form face centered cubic structures (FCC), however some studies indicate that duplex alloys, also composed of a body center cubic phase (BCC) have excellent mechanical properties. In this project will be presented thermodynamic calculations that indicate compositions from the CrCoNi system as promising for the formation of a duplex structure. Here, the production one composition will be proposed in order to understand the feasibility of manufacturing CFC + CCC duplex alloys in the CrCoNi system. This composition is the alloy Cr51,5Ni33,5Co15. It will be studied in the homogenized and as-cast conditions by optical microscopy, X-ray diffraction, Vickers microhardness and a preliminary cold rolling test. The results of this work will contribute to evaluate the production potential and mechanical properties of duplex alloys in the CrCoNi system.
Production and characterization of duplex multicomponent alloy of CrCoNi system with composition Cr51.5Ni33.5Co15
Keywords: Ligas de alta entropia; Sistema CrCoNi; Estrutura duplex; Caracterização; Fases CCC e CFC; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA